The Correlation of Cosmetic use with Incident of Acne Vulgaris - Ago Harlim; Mery Carolina Tiovani; Kelvin Kelvin (Indonesian Journal of Global Health Research, 2025)
Acne vulgaris (AV), commonly known as acne, is a common skin problem that can cause skin damage. AV is a form of chronic inflammation of the pilosebaceous follicles due to blockage. According to the Global Burden of Disease (GBD), 85% of people, including young adults aged 12 to 25, have experienced AV. One factor that often exacerbates the occurrence of AV is the use of cosmetics with comedogenic properties. Therefore, the purpose of this study was to determine whether there is a relationship between cosmetic use and the occurrence of AV in female students of the Faculty of Medicine, Christian University of Indonesia class of 2023. Observational analysis research with a cross-sectional approach was used in this study. A total of 85 samples were obtained using the research method, namely purposive sampling. Data collection was conducted at a single point in time to explore cosmetic use related to AV events. Data analysis using univariate and bivariate techniques. From the total, 76 respondents (89.4%) experienced AV and 9 respondents (10.6%) didn’t. The Fisher Exact Test results obtained a P value > 0.05, this indicates that there was no significant relationship between cosmetic use and AV incidents in these female students.